Health Behavior and Associated Factors in Young Adult Cancer Patients - Stroske, Isabelle; Geue, Kristina; Friedrich, Michael; Sender, Annekathrin; Schmidt, Ricarda; Richter, Diana; Leuteritz, Katja (Frontiers in Psychology, 2021)
Objectives: Having cancer in young adulthood increases the risk of adverse long-term health effects. These risks can be influenced by one’s health behavior (HB). The aim of this study is therefore to investigate the presence of health behavior in adolescents and young adults (AYAs) and to identify associated factors. Design: Young cancer patients (18-39 years old at time of diagnosis) were surveyed at baseline and 12 months later via online or as a paper-pencil version. Methods: A spectrum of indicators for HB were assessed via seven items from the Questionnaire of Multiple Health Behavior. Multiple linear regression analyses were conducted to determine factors associated with patients’ HB indicators. Results: 514 AYAs (75% women) reported the highest level of health-conscious behavior for for “avoidance of consumption of nicotine”, “follow medical recommendations”, and “being considerate in road traffic”. Less health-conscious behavior was reported for “keeping an appropriate and balanced diet” and “physical activity”. Significant improvements from baseline to the follow-up were observed for “regularly attending health screening” (Hedges’ g =0.44). The analyzed predictors explained up to 10 %of the HB- indicators. Women reported significantly more health-conscious behavior than men in four out of seven HB- indicators. Higher quality of life was associated with more health behavior in 3 out of seven HB-indicators. Conclusion: Findings show a predominantly health-conscious lifestyle in AYA cancer patients, though we also found harmful behavior which needs to be better approached—e.g., through improving AYAs’ health education. AYA men should be particularly targeted in specific prevention and health promotion measures. Future work should identify other factors associated with HB to evaluate targets for intervention.